Limonoids From the Genus Melia (Meliaceae): Phytochemistry, Synthesis, Bioactivities, Pharmacokinetics, and Toxicology - Fan, Wenxiang; Fan, Linhong; Wang, Zhengtao; Yang, Li (Frontiers in Pharmacology, 2022)
Limonoids, as the vital bioactive chemical compounds in genus Melia plants, have attracted great attention owning to their exclusive structure characteristics and remarkable biological activity. These compounds can be usually classified into two categories including rings intact group and ring C-seco group. Benefiting from the development of separation and analysis technology, more than two-hundreds of limonoids have been isolated and identified from this genus. There is growing evidence that limonoids from genus Melia possess diverse pharmacological activities, especially anti-cancer effects, insecticidal activities and anti-botulismic effects. Toosendanin, one of the paramount limonoids, was considered as the pivotal bioactive marker in two medicinal herbs including Melia toosendan Sieb. et Zucc and Melia azedarach L.. In particular, limonoids are found to exhibit non-negligible toxic effects, which needs a further research. Besides, lack of clinical research data seriously hinders its further development and utilization, thus necessary clinical trials should be taken into consideration. In this review, we systematically summarized the phytochemical compounds and their synthesis methods, pharmacological activities and structure-activity relationship, pharmacokinetics, and toxicology of genus Melia derived limonoids. We believe this up-to-date review could provide scientific evidences on the application of limonoids as health beneficial agents in future clinical practice.